Bredigite Reinforced Electrospun Nanofibers for Bone Tissue Engineering - Monireh, Kouhi; Mohammadhossein, Fathi; Venugopal, Jayarama Reddy; Seeram, Ramakrishna (Elsevier, 2019)
In this study, bredigite nanoparticles were treated with an organosilane coupling agent to enhance its dispersability and compatibility with polymers. The polyhydroxybutyrate-co-hydroxyvaletare (PHBV) nanofibrous scaffolds containing treated bredigite (T-BR) nanoparticles were developed using electrospinning technique. It was found that pre-treating of bredigite was effective in enhancing nanoparticles dispersion both in the solution and in the PHBV matrix. Mechanical properties of the PHBV nanofibrous scaffolds were remarkably improved by incorporation of T-BR nanoparticles. The results also demonstrated that bioactivity and biodegradability rate of PHBV nanofibrous scaffolds were greatly altered by addition of BR and T-BR nanoparticles. Our study demonstrated that incorporation of T-BR nanoparticles within PHBV nanofibers may improve its mechanical performance and bioactivity, making it more appropriate materials for bone tissue engineering applications.